Perancangan Perbaikan Pelayanan Bongkar Muat Dermaga X Dengan Menggunakan Extend Simulasi - Misra Hartati; Ahmad Kurniawan; Melfa Yola; Merry Siska (Universitas Katolik Parahyangan, 2019)
Large-scale logistics companies deliver products using sea transportation effectively. Company X as one of the pioneer port containers service still has limitations both from minimal stacking capacity and limited equipment, 1 HMC unit and 1 unit reach adapter. The number of containers increases from 2014-2017, but the availability of tools and facilities that needed continue to cause overcapacity problem. This paper aims to determine the yard occupancy ratio (YOR), berth occupancy ratio (BOR) and utility equipment that are in accordance with the standards to prevent overcapacity at port X until 2020. This study uses extend simulation method to make improvements and analysis of conditions that running, the results of the study are recommendations for the addition of 2 units of transport and the addition of reach units of 2 units. For the YOR value, additional capacity from 2,046 TEUs was made to 3,800 TEUs so that the initial maximum YOR was 139.8% to 75.3%, while BOR still in maximum BOR capacity which is 24.0%.Keywords: Container, Discrete Event Simulation, ExtendSim, Port